The Ser460Pro mutation in recombinant protein S Heerlen does not affect its APC-cofactor and APC-independent anticoagulant activities - Koenen, Rory R.; Gomes, Lucio; Tans, Guido; Rosing, Jan; Hackeng, Tilman M. (Thrombosis and Haemostasis, 2004)
Protein S is a vitamin K-dependent plasma protein that functions as an APC-cofactor, but also exhibits anticoagulant activity in the absence of APC. The Heerlen polymorphism of protein S is characterized by a Ser460Pro substitution and lacks glycosylation at Asn458. It is associated with decreased protein S levels due to selective deficiency of free protein S Heerlen.To understand the lack of thrombotic complications associated with the protein S Heerlen mutation, we compared recombinant protein S Heerlen, wild type (wt) protein S and plasmaderived protein S. wt-Protein S and protein S Heerlen each bound 1:1 to C4BP with dissociation constants of 0.27 and 0.33 nM, respectively. Both wt-protein S and protein S Heerlen, either free or in complex with C4BP, were equally active as prothrombinase inhibitors in the absence of APC. All three protein S preparations stimulated APC-catalyzed inactivation of normal FVa, FVa Leiden and FVIIIa to the same extent. If extrapolated to plasma, it is not likely that the decreased free protein S levels in carriers of the protein S Heerlen mutation are compensated by an increased anticoagulant activity of protein S Heerlen-C4BP complexes. It is possible that an unrecognized plasma factor selectively enhances the anticoagulant activity of protein S Heerlen. If not, the reduction of free protein S levels in heterozygous protein S Heerlen-carriers combined with (low) normal total protein S levels apparently minimally affects the total anticoagulant activity of protein S (APC-cofactor and APC-independent activity) and hence is not associated with increased risk of venous thrombosis.
Keywords: Factor VIII; factor V; factor V Leiden; protein C/S pathway; protein function/activity